Incidence, clinical features, management and outcomes of ANCA-associated vasculitis in pregnancy- a systematic literature review - Ashok, Apurva; Russell, Laura; Dey, Mrinalini; Kouranloo, Koushan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitides (AAV) are rare multi-system conditions, usually presenting in older age groups. However, younger individuals are also affected. The average increase of childbearing age and lack of studies in pregnancy necessitates this comprehensive review of data to guide the management of AAV in pregnancy. This systematic review (SR) aimed to summarise the incidence, clinical features, management and maternal and foetal outcomes in female patients with AAV.Methods: The protocol was registered on PROSPERO (CRD42023437482). Articles published in Medline, Embase and Cochrane Databases from 1946 until June 2023 were included. Single case reports, reviews and conference abstracts were excluded. Articles meeting inclusion criteria were examined by two authors. Data on demographics, treatment, clinical features, flares during pregnancy and maternal and foetal outcomes were extracted.Results: Eight studies were included, detailing 82 pregnancies in 64 women. The most common drugs used for remission induction pre-conception were cyclophosphamide, rituximab, prednisolone and azathioprine. Serious maternal complications in pregnancy included progressive tracheal/subglottic stenosis (n=5), renal disease (n=2), preeclampsia (n=10) and miscarriages (n=5). Foetal anomalies were rare (n=5). The mean birth weight was 3.37kgs and mean gestation age was 38.26 weeks. No maternal deaths or vasculitis in newborns were reported. Conclusions: Patients can have positive maternal and foetal outcomes following strong induction therapy, vigorous monitoring and prompt treatment of flares during pregnancy. Serious complications and flares are not associated with worse outcomes for newborns.